Conscious Capitalism - Mackey, John; Sisodia, Raj (HighBridge, 2014)
In this New York Times and Wall Street Journal bestseller, Whole Foods Market cofounder John Mackey and professor and Conscious Capitalism, Inc. cofounder Raj Sisodia argue for the inherent good of both business and capitalism. Featuring some of today's best-known and most successful companies, they illustrate how these two forces can-and do-work most powerfully to create value for all stakeholders, including customers, employees, suppliers, investors, society, and the environment.Conscious Capitalism helps us better understand how companies such as Southwest Airlines, Costco, UPS, Panera, Patagonia, Google, The Container Store, and many others, use four specific tenets-higher purpose, stakeholder integration, conscious leadership, and conscious culture and management-to build strong businesses, advance capitalism toward its highest potential, and foster a more positive environment for all of us.